Quality raw jute seed production: Prospect and Retrospect - Bera, A; Chowdhury, H; Ramasubramanian, T; Mahapatra, B S (Indian Farming, 2015)
There are several issues that need to be addressed to make the raw jute farming a viable, remunerative and competitive one. Availability of quality jute seed is of major concern nowadays. Although West Bengal contributes more than 80% of the fibre production, Andhra Pradesh and Maharastra take the lead in jute seed production. It is quite common that the jute seed does not reach the market in time due to the physical distance. This creates an artificial shortage of seed and abnormal price hike, which ultimately affects the resource-poor jute farmers. Therefore, it is imperative to try seed production in non-traditional, fibre producing states of India. The â€œLate Jute Seed Production Technologyâ€ may be considered for jute seed production in fibre producing states of India, which may pave the way for sustainable jute farming in India.